IDEAL AND REAL LEADERSHIP OF NURSES IN INTENSIVE CARE UNITS AT PRIVATE AND PUBLIC HOSPITALS - Alexandre Pazetto Balsanelli; Isabel Cristina Kowal Olm Cunha (Universidade Federal do Paraná, 2016)
The aim of this study was to analyze differences in styles of ideal and real leadership of nurses in intensive care units at private and public hospitals. A cross-sectional study was carried out in four intensive care units (two private and two public) in the city of São Paulo, state of São Paulo, Brazil. The sample consisted of 66 pairs (nurses and nursing technicians) randomly chosen. Data were collected between January and April of 2013. The nurses answered the questionnaire Grid & Leadership in Nursing - ideal behavior. The nursing technicians answered the questionnaire Grid & Leadership in Nursing - real behavior, considering the nurse who chose them. Among the 66 nurses, 65 (98.5%) considered the style 9.9 as ideal and 42 (63.6%) were evaluated as 9.9 by the nursing technician. There were not differences between nurses' ideal and real styles of leadership in intensive care units at private and public hospitals (p=0.67).